(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This study examines how speech acts that are direct and indirect operate in English and in Uzbek, focusing on their grammatical shapes, pragmatic roles, and cultural motivations. The paper contrasts strategies speakers use to convey requests, commands, refusals and opinions, and it discusses how conventions of politeness and social position alter linguistic choices. The theoretical grounding relies on classical speech-act theory (Austin and Searle) and on observations by Uzbek scholars who investigate language behavior in local communicative contexts. The findings stress that pragmatic competence—knowing how to choose forms appropriately—is essential for cross-cultural interaction and language instruction.